Photoactive Conjugated Polymer‐Based Hybrid Biosystems for Enhancing Cyanobacterial Photosynthesis and Regulating Redox State of Protein. (20th November 2020) - Zeng, Yue; Zhou, Xin; Qi, Ruilian; Dai, Nan; Fu, Xuancheng; Zhao, Hao; Peng, Ke; Yuan, Haitao; Huang, Yiming; Lv, Fengting; Liu, Libing; Wang, Shu
Abstract: Constructing artificial hybrid biosystems, comprising of organisms and organic non‐biological functional material, will afford promising opportunities to achieve brand new or enhanced functions. In this work, a hybrid biosystem is designed and constructed by electrostatically recombining photoactive cationic poly(fluorene‐ co ‐phenylene) derivative (PFP) with a cyanobacterium ( Synechococcus sp. PCC7942, Syne ) for enhancing its photosynthesis and regulating exogenous redox state of protein. The light utility efficiency of Syne is significantly improved assisted by the excellent ultraviolet light‐harvesting ability of PFP, which accelerates electron‐transfer rate in non‐cyclic electron transport chain, and further augments the light‐dependent reaction in photosynthesis. As a result, O2, NADPH, and ATP production in the light‐dependent reaction are increased by 52.8%, 47.9%, and 27.2%, respectively. Moreover, the extracellular electron transfer property of Syne is able to realize electronic communication with external circumstances. Specifically, the electrons exported from Syne can reduce exogenous oxidized cytochrome c (Cyt c ) and adsorbed PFP has the ability to regulate the reduction degree of Syne to Cyt c . This work reports an ideal design of a conjugated polymer‐based hybrid biosystem, providing a strategy to promote photosynthesis and regulate the redox state of protein. Abstract : A new hybrid biosystem is designed by combing Synechococcus sp. ( Syne ) with a conjugated polymer to promote photosynthesis and regulate the redox state of exogenous cytochrome c . The conjugated polymer can absorb additional ultraviolet light to improve light utility efficiency and augment photosynthesis of Syne . Moreover, the conjugated polymer can also affect the extracellular electronic communication of Syne to regulate the reduction degree of cytochrome c .